An empirical analysis of efficiency and profitability determinants for Chinese banking - DING, WEI (2018)
This paper aims to investigate the X-efficiency and profitability of Chinese banks and uses the data of 210 commercial banks comprises state-owned banks, joint- equity commercial banking, city commercial banking as well as foreign banks from the period 2013 to 2017. For the efficiency of Chinese banks, the average X-efficiency score is 0.856 during the sample period which conducted by the method of SFA (stochastic frontier approach). In terms of the stage of bank performance, the variables about bank-specific, industry-specific, and macroeconomic are taken into analysis for the correlation with bank performance by the measure of system GMM. And it concludes that more liquidity assets, higher X-efficiency score, and inflation rate may contribute to the generation about more profits while the tax burden is negatively correlated with bank profitability.